2018
DOI: 10.1002/pon.4726
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐utility analysis of meaning‐centered group psychotherapy for cancer survivors

Abstract: BackgroundMeaning-focused coping may be at the core of adequate adjustment to life after cancer. Cancer survivors who experience their life as meaningful are better adjusted, have better quality of life and psychological functioning. Meaning-Centered Group Psychotherapy for Cancer Survivors (MCGP-CS) was designed to help patients to sustain or enhance a sense of meaning and purpose in their lives. The aim of the proposed study is to evaluate the effectiveness and cost-effectiveness of MCGP-CS.Methods/DesignSur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…1 Data from this equivalence RCT indicated that T-CBT was of equivalent effectiveness to gold standard face-to-face Treatment as Usual CBT (TAU-CBT) in terms of patient reported psychological symptoms and benefits. Data on economic aspects of psychological interventions within oncology care remain sparse, however, [2][3][4][5] and require further investigation. While T-CBT and TAU-CBT are both of proven effectiveness in reducing psychological morbidity, the question arises of whether important cost implications exist both in terms of one therapy model compared to another, but also for the healthcare sector more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…1 Data from this equivalence RCT indicated that T-CBT was of equivalent effectiveness to gold standard face-to-face Treatment as Usual CBT (TAU-CBT) in terms of patient reported psychological symptoms and benefits. Data on economic aspects of psychological interventions within oncology care remain sparse, however, [2][3][4][5] and require further investigation. While T-CBT and TAU-CBT are both of proven effectiveness in reducing psychological morbidity, the question arises of whether important cost implications exist both in terms of one therapy model compared to another, but also for the healthcare sector more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…It is a brief intervention that is effective and cost-effective. 8,11 Some of its effects linger on for 1 or even 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…MCGP-CS participants reported better positive relations (SPWB) at long term, but did not report that these relations became a stronger (13) 59 (12) 62 (16) 63 (13) 57 (14) 59 (15) 61 (14) 58 (13) 59 (17) 63 (12) 58 (11) .030* .011* Goal-orientedness 69 (20) 71 (17) 72 (17) 74 (20) 72 (16) 63 (23) 66 (17) 69 (18) 66 (18) 66 (20) 73 (17) 68 ( Corrected for baseline score.…”
Section: Study Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…28 Among the few cost-utility studies of psychosocial services, the EQ-5D was used by Strong et al to evaluate nurse-delivered collaborative care for the management of depression, 29 Duarte et al who evaluated the cost-effectiveness of a collaborative care program for major depression, 15 and most recently by van der Spek et al who assessed the cost-effectiveness of meaningcentred group psychotherapy for cancer survivors. 30 Chatterton et al used the AQoL-8D in the economic evaluation of a psychological intervention for high distress cancer patients and caregivers. 31 Nevertheless, these instruments are generic (ie, not disease specific), and therefore, their ability to accurately measure HRQoL in cancer patients is questionable.…”
Section: Dieng Et Al 9 2016mentioning
confidence: 99%